2023
DOI: 10.1111/imr.13184
|View full text |Cite
|
Sign up to set email alerts
|

Surfing on the waves of the human γδ T cell ontogenic sea

Abstract: γδ T cells are, like αβ T cells and B cells, lymphocytes that can rearrange gene segments at the DNA level with the potential to generate a set of highly diverse antigen receptors. 1,2 This tripartite division of immune cells possessing somatically diversified antigen receptors (γδ T cell receptor (TCR), αβ TCR and B cell receptor (BCR)) is a fundamental pillar of the immune system in jawed vertebrates (Gnathostomata). 3 Indeed, this division is traced back even in distant species with cryptic lymphocyte linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 211 publications
0
20
0
Order By: Relevance
“…Their review is distinguished by an elegant genetic analysis of genome‐wide transcription data that has become available in recent years. As noted above, the single cell human sequencing studies have also revealed differences in gene expression in waves of human γδ T cell development as discussed by Sanchez et al 22 …”
Section: The Genetic Basis For Layered Immune System Developmentmentioning
confidence: 80%
See 3 more Smart Citations
“…Their review is distinguished by an elegant genetic analysis of genome‐wide transcription data that has become available in recent years. As noted above, the single cell human sequencing studies have also revealed differences in gene expression in waves of human γδ T cell development as discussed by Sanchez et al 22 …”
Section: The Genetic Basis For Layered Immune System Developmentmentioning
confidence: 80%
“…Their review is distinguished by an elegant genetic analysis of genome-wide transcription data that has become available in recent years. As noted above, the single cell human sequencing studies have also revealed differences in gene expression in waves of human γδ T cell development as discussed by Sanchez et al 22 At least two models can be formulated to explain the layering of immune and hematopoietic system development (Figure 1). The An alternative "Molecular Layering model" is presented in the review from Burt and McCune.…”
Section: The G Ene Ti C Ba S Is For L Ayered Immune Sys Tem De Velopmentmentioning
confidence: 96%
See 2 more Smart Citations
“…11,12 In fact, previous studies reported that reduced thymic activity leads to changes in the immune cell composition in patients with CHD, including lower total numbers of T cells, [13][14][15] lower frequencies of naïve CD4 + and CD8 + αβ T cells, 16 and less diversity in the T cell receptor (TCR) repertoire of αβ T cells. 17 However, T cells that predominantly develop in the prenatal thymus, 18,19 have not been the focus of studies in this context.…”
Section: Introductionmentioning
confidence: 99%